2006
DOI: 10.1523/jneurosci.1560-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Survival and Death Signaling in Basal Forebrain Neurons: Roles of Neurotrophins and Proneurotrophins

Abstract: Proneurotrophins bind with high affinity to p75 neurotrophin receptor (p75 NTR ) and lack the capacity to bind Trk receptors, suggesting that proneurotrophins can elicit apoptosis via p75 NTR even in cells expressing survival-promoting Trk receptors. In the CNS, basal forebrain (BF) neurons are particularly vulnerable to degeneration in Alzheimer's disease, and are among the few populations of brain neurons that express p75 NTR throughout life. These neurons also express Trk receptors and may be concomitantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(222 citation statements)
references
References 59 publications
(96 reference statements)
8
210
2
1
Order By: Relevance
“…The role of p75 NTR as an apoptotic receptor is well established as it has been shown to facilitate developmental cell death of peripheral sympathetic neurons and early retinal neurons (8,(24)(25)(26). p75 NTR has also been implicated in cell loss following various forms of CNS injury and promotes apoptosis of cortical and hippocampal neurons, basal forebrain neurons, oligodendrocytes, and photoreceptor cells (8,(27)(28)(29)(30)(31). Overall, the functional role of p75 NTR in neuronal death is best understood in neurons that endogenously express this receptor.…”
Section: Resultsmentioning
confidence: 99%
“…The role of p75 NTR as an apoptotic receptor is well established as it has been shown to facilitate developmental cell death of peripheral sympathetic neurons and early retinal neurons (8,(24)(25)(26). p75 NTR has also been implicated in cell loss following various forms of CNS injury and promotes apoptosis of cortical and hippocampal neurons, basal forebrain neurons, oligodendrocytes, and photoreceptor cells (8,(27)(28)(29)(30)(31). Overall, the functional role of p75 NTR in neuronal death is best understood in neurons that endogenously express this receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that proneurotrophins binding to p75 mediates cell death after injury or neurodegenerative diseases such as Alzheimer's dementia (Harrington et al 2004;Peng et al 2004;Pedraza et al 2005;Volosin et al 2006). Pro-neurotrophins are produced and then cleaved by furin and other proteases to produce the mature neurotrophin (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pro-neurotrophins are produced and then cleaved by furin and other proteases to produce the mature neurotrophin (Lee et al 2001). The precursor form of NGF, proNGF is responsible for inducing apoptotic death in particular cellular contexts (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Volosin et al 2006). Proneurotrophins, such as proNGF and proBDNF, preferentially interact with sortilin together with p75 to form a complex capable of activating an apoptotic cascade (Lee et al 2001;Nykjaer et al 2004;Teng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in peripheral neurons have established a positive effect of p75 NTR on neurotrophin binding to Trk receptors, enhancing both ligand affinity and selectivity, and thereby strengthening survival responses (Lee et al, 1994;Rydén et al, 1997). In basal forebrain cholinergic neurons, however, simultaneous engagement of p75 NTR and Trk receptors through concomitant stimulation with pro-and mature neurotrophin ligands resulted in death, not survival, of these neurons (Volosin et al, 2006), indicating that p75 NTR signaling was dominant in this case. It would be interesting to test whether pro-neurotrophins can kill peripheral neurons in the absence or presence of their mature counterparts.…”
Section: Multisubunit Receptor Complexes For Neurotrophic Factorsmentioning
confidence: 99%